Left frontal anodal tDCS increases approach motivation depending on reward attributes. (October 2018) - Ohmann, Hanno Andreas; Kuper, Niclas; Wacker, Jan
Abstract: Background: A growing body of literature indicates a correlation between asymmetrical activity of frontal brain sites and approach vs. withdrawal motivation. Yet the causal status of this relationship is presently unclear. Here we examined the effect of anodal tDCS applied over the left dorsolateral prefrontal cortex (dlPFC) on approach motivation, operationalized as effort allocation during the Effort-Expenditure for Reward Task (EEfRT). Hypothesis: We expected left frontal anodal transcranial direct current simulation (tDCS) to increase participants' willingness to allocate more effort during the EEfRT. Based on previous research, we expected this effect to be strongest on trials with low probability of reward attainment. Methods: 60 right-handed neurologically and psychologically healthy participants (63% female) aged 18–35 were tested in a counterbalanced within-subject design. Participants were invited to our lab twice to complete two 15-min blocks of the EEfRT on each study day, randomly assigned to either an anodal tDCS or a SHAM condition. Results: No main effect of stimulation condition was found, however the interactions of stimulation condition and both probability of reward attainment and reward magnitude reached significance. These interactions indicated that left frontal anodal tDCS specifically increased the percentage of hard task choices (HTC) in trials with low probability of reward attainment and in trials with high reward magnitude. Discussion: The observation of an increasing effect of left frontal anodal tDCS on effort expenditure for reward as indicated by HTC supports the idea of a causal relationship between asymmetric activity of frontal brain sites and approach motivation and hints at moderating effects of task-features on the effects of tDCS. Highlights: Anodal tDCS stimulation over the left dlPFC increases approach motivation. Stimulation effects show when large rewards are at stake or rewards are unlikely. Results hint at a causal role of asymmetric frontal brain activity in motivation.